(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The caste system was divided into four varnas. At the top are the brahmins, next are the Kshatriyas, underneath them are vaishyas, and finally at the end of the list are Shudras.A fifth category falls outside the varna system and consists of those known as “untouchables” or Dalits; they are often assigned tasks too ritually polluting to merit inclusion within the traditional varna system. The tasks they perform and their status in the caste system are not socially recognized. Dalits are also known as “untouchables” as they are seen as polluting for the higher caste people. If a member of the higher caste is touched by a Dalit or even their shadow is crossed by a Dalit, they consider themselves polluted and go through a rigorous religious process to be cleansed. After more than 75 years of Indian Independence, the condition of Dalit can be seen or read through the different newspaper or media-source.